2013
DOI: 10.1038/ncomms3909
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine is required for sustained inflammasome activation via the A2A receptor and the HIF-1α pathway

Abstract: Inflammasome pathways are important in chronic diseases, but it is not known how the signalling is sustained after initiation. Inflammasome activation is dependent on stimuli such as LPS and ATP that provide two distinct signals resulting in rapid production of IL-1β, with lack of response to repeat stimulation. Here we report that adenosine is a key regulator of inflammasome activity, increasing the duration of the inflammatory response via the A2A receptor. Adenosine does not replace signals provided by stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 32 publications
(46 reference statements)
6
88
2
Order By: Relevance
“…This low cytoplasmic Ca 2ϩ concentration in IL-10 Ϫ/Ϫ DCs might be mediated by the inhibited P2X7 receptor. Intracellular cAMP regulates the NLRP3 inflammasome; studies show that cAMP suppresses NLRP3 inflammasome activation through the inhibition of inflammasome assembly (24,39). Our results showed an inverse correlation between the levels of cAMP and the presence or absence of IL-10, suggesting that Chlamydia-pulsed IL-10 Ϫ/Ϫ DCs had increased levels of cAMP synthesis, which might repress NLRP3 inflammasome formation.…”
Section: Discussionsupporting
confidence: 58%
“…This low cytoplasmic Ca 2ϩ concentration in IL-10 Ϫ/Ϫ DCs might be mediated by the inhibited P2X7 receptor. Intracellular cAMP regulates the NLRP3 inflammasome; studies show that cAMP suppresses NLRP3 inflammasome activation through the inhibition of inflammasome assembly (24,39). Our results showed an inverse correlation between the levels of cAMP and the presence or absence of IL-10, suggesting that Chlamydia-pulsed IL-10 Ϫ/Ϫ DCs had increased levels of cAMP synthesis, which might repress NLRP3 inflammasome formation.…”
Section: Discussionsupporting
confidence: 58%
“…4C), affecting subsequent PGN/NOD2 interaction, which may impair IL-1b secretion. However, in contrast, others showed that adenosine signaling was required to induce IL-1b secretion through the A2aR (45,49). Thus, it would be interesting to investigate the role of adenosine produced by S. aureus on IL-1b secretion.…”
Section: Discussionmentioning
confidence: 99%
“…NPCs contained liver endothelial, stellate, and Kupffer cells; all were maintained in DMEM containing 10% FBS. Mouse macrophages were isolated and maintained as previously described (36). Mouse primary cholangiocytes were provided by Carlo Spirli (Yale University) as previously described (37).…”
Section: Methodsmentioning
confidence: 99%